ANALYSIS OF IMPLEMENTATION OF ADDITIONAL EDUCATION PROGRAMMES FOR CHILDREN (AS EXEMPLIFIED BY PROGRAMMES ON PREPARATION FOR DRIVING) - Anna Ter-Grigor'yants; Anna Babich; Elena Mezentseva (Вестник Северо-Кавказского федерального университета, 2022)
In the following article results of a complex analysis of implementation ofexisting academic programmes on preparation for driving in organizations for additional education of children are presented; requirements for the concept of preparation for driving are systematized, which includes preparation based on multimedia educational resources; training, educational and learning tasks for preparation for driving in organizations for additional education of children are formulated.